Perceptions of stakeholders on the environmental degradation of the Sibunag watershed in Guimaras - Arias, Evan Anthony V. (1998.)
The Sibunag River Basin is the largest river basin in the island-province of Guimaras.
Special Problem - (Cert. in Environmental Resource Mgt.) - U. P. in the Visayas.
Keywords: Sibunag watershed -- Environmental degradation